Changes in the Profile of Antibiotic Prescriptions by Dentists in Brazil during the Pandemic - Fernando de Sá Del Fiol; Isaltino Pereira de Andrade-Jr; Marcus Tolentino da Silva; Silvio Barberato-Filho; Luciane Cruz Lopes; Cristiane de Cassia Bergamaschi (International Journal of Dentistry)
During the COVID-19 pandemic, people worldwide, including the scientific community, were insecure and fearful. The lack of vaccines at the beginning of the pandemic and the high mortality rate led to a search for alternative treatments for COVID-19. Among these proposals, a postulated activity of azithromycin was frequently studied in early treatment. In view of this, many countries saw an increase in the consumption of this antibiotic. Thus, the objective of this study was to evaluate, in Brazil, whether there was an increase in azithromycin prescriptions made by dentists, as they may have been prescribing this antibiotic as a probable treatment for COVID-19. This is an interrupted time series that analyzed antimicrobial prescriptions data between January 2014 and July 2021. The data were taken from the National System of Controlled Products Management, and pre- and postpandemic periods were compared. To assess changes in azithromycin consumption, Joinpoint regression and analysis of variance, followed by Dunnett’s test, were used. More than 38 million prescriptions written during the period were analyzed. Amoxicillin (72.3%), azithromycin (18.0%), cephalexin (6.1%), and metronidazole (3.58%) were the most prescribed antibiotics. At the beginning of the pandemic, there was a drop in amoxicillin prescriptions motivated by a decrease in consultations, but conversely, in less than three months, azithromycin prescriptions grew by more than 100%. The exaggerated use of this antibiotic during the pandemic will certainly have consequences in the short and medium term on indicators of bacterial resistance. The use of guidelines and respect for the therapeutic protocols of government agencies should be fundamental for collective and strategic action in the fight against health emergencies.